2000
DOI: 10.1128/iai.68.9.5299-5305.2000
|View full text |Cite
|
Sign up to set email alerts
|

Does Inhibition of Tumor Necrosis Factor Alpha Affect Chlamydial Genital Tract Infection in Mice and Guinea Pigs?

Abstract: The role of tumor necrosis factor alpha (TNF-␣) in host defense against chlamydial infection remains unclear. In order to further evaluate the relevance of TNF-␣ to host resistance in chlamydial genital tract infection, we examined the effect of local inhibition of the TNF-␣ response in normal C57 mice and in interferon gamma gene-deficient C57 mice infected intravaginally with the mouse pneumonitis agent of Chlamydia trachomatis. Since the guinea pig model of female genital tract infection more closely approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Increased neutrophil influx into the lower genital tracts of C57 and BALB/c mice paralleled the high TNF-␣ and IL-1␤ responses of these mice during the first week of infection. However, our previous data on depletion of TNF-␣ indicate that neutrophil chemotaxis is effectively induced in its absence (8). Moreover, the largest numbers of neutrophils were seen in the lower genital tract of the BALB/c strain during the first week of infection and were associated with significantly increased levels of MIP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Increased neutrophil influx into the lower genital tracts of C57 and BALB/c mice paralleled the high TNF-␣ and IL-1␤ responses of these mice during the first week of infection. However, our previous data on depletion of TNF-␣ indicate that neutrophil chemotaxis is effectively induced in its absence (8). Moreover, the largest numbers of neutrophils were seen in the lower genital tract of the BALB/c strain during the first week of infection and were associated with significantly increased levels of MIP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor alpha and interleukin 1␤ (IL-1␤) levels are markedly elevated in the C57BL/6 mice relative to C3H/ HeN mice, and there are correlative data related to a prolonged presence of neutrophils and coincident increases in chemokine macrophage inflammatory protein 2 in the susceptible strains (8,9). Apoptosis and Toll-like receptor 2 signaling have both also been implied in initiating and regulating inflammatory damage in this model (10,32).…”
mentioning
confidence: 89%
“…We have recently reported a role for iNOS in protection from chronic chlamydial disease in mice (32). In addition, Darville et al have shown a positive correlation between the production of tumor necrosis factor alpha early in infection and resistance to disease (11). In contrast, increased and sustained macrophage inflammatory protein 2 production and the corresponding neutrophil influx were associated with susceptibility to disease (12).…”
mentioning
confidence: 98%